Zoonotic Babesia: A scoping review of the global evidence. - Kaitlin M Young; Tricia Corrin; Barbara Wilhelm; Carl Uhland; Judy Greig; Mariola Mascarenhas; Lisa A Waddell (PLoS ONE)
Background Babesiosis is a parasitic vector-borne disease of increasing public health importance. Since the first human case was reported in 1957, zoonotic species have been reported on nearly every continent. Zoonotic Babesia is vectored by Ixodes ticks and is commonly transmitted in North America by Ixodes scapularis, the tick species responsible for transmitting the pathogens that also cause Lyme disease, Powassan virus, and anaplasmosis in humans. Predicted climate change is expected to impact the spread of vectors, which is likely to affect the distribution of vector-borne diseases including human babesiosis. Methods A scoping review has been executed to characterize the global evidence on zoonotic babesiosis. Articles were compiled through a comprehensive search of relevant bibliographic databases and targeted government websites. Two reviewers screened titles and abstracts for relevance and characterized full-text articles using a relevance screening and data characterization tool developed a priori. Results This review included 1394 articles relevant to human babesiosis and/or zoonotic Babesia species. The main zoonotic species were B. microti, B. divergens, B. duncani and B. venatorum. Articles described a variety of study designs used to study babesiosis in humans and/or zoonotic Babesia species in vectors, animal hosts, and in vitro cell cultures. Topics of study included: pathogenesis (680 articles), epidemiology (480), parasite characterization (243), diagnostic test accuracy (98), mitigation (94), treatment (65), transmission (54), surveillance (29), economic analysis (7), and societal knowledge (1). No articles reported predictive models investigating the impact of climate change on Babesia species. Conclusion Knowledge gaps in the current evidence include research on the economic burden associated with babesiosis, societal knowledge studies, surveillance of Babesia species in vectors and animal hosts, and predictive models on the impact of climate change. The scoping review results describe the current knowledge and knowledge gaps on zoonotic Babesia which can be used to inform future policy and decision making.